The effect of addition of powder jujube (Ziziphus jujuba Mill.) fruit at different rates into mixed diets on antioxidant and some blood parameters of broiler chickens* - Arslan, S; Parlak AK, T; Guler Ekmen, E; Kkarakoc, S; Çiftçi, M (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was conducted to determine the effects of addition of jujube (Ziziphus jujuba Mill.) fruit at different rates into the mixed feed on intestinal morphology, antioxidant and some blood parameters of broiler chickens. A total of 160 male broiler chickens (Ross-308), including 40 in each group, were used in the study. The groups were divided into 4 sub-groups, each of which include 10 broiler chickens. The study groups were the control group ( the group without jujube fruit), the H-0.5% group (the group with 0.5% jujube fruit), the H-1 group (the group with 1% jujube fruit), and the H-2 group (the group with 2% jujube fruit). At the end of the experiment (42nd day), the control group had the highest levels of blood glucose, triglycerides, total cholesterol, VLDL cholesterol, ALT, AST, and uric acid, and the lowest level of creatine (P<0.05). While the lowest MDA level was detected in the H-2 group (P<0.001), the highest GSH (P<0.01) and CAT (P<0.05) levels were observed in the H-1 and H-2 groups. The control group also had the lowest values for villus height and crypt depth and the highest values for villus height/crypt depth (P<0.001). As a result, it was concluded that jujube fruit, which is mainly used for its antioxidant properties, can be used in poultry compound feeds especially at the level of 1% due to its positive effects on antioxidant and blood parameters and intestinal morphology.